2006
DOI: 10.1029/2006gl027819
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution and abundance of red snow algae on the Harding Icefield, Alaska derived from a satellite image

Abstract: [1] Red snow caused by algal bloom is common on glaciers and snowfields worldwide. Description of spatial distributions of snow algal blooms is important for understanding snow algae's unique life in an extremely cold environment and for determining the effect of algae through the reduction of surface albedo. Here we present the spatial distribution of red snow algae on the Harding Icefield, Alaska retrieved from a satellite image. Field observations on the icefield conducted in August 2001 revealed visible re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
112
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(120 citation statements)
references
References 17 publications
7
112
1
Order By: Relevance
“…The spectrum at 333 ppm was similar in shape, but with lower values of reflectance, to a theoretical spectral albedo of snow with very high densities of algae 18 . The spectrum at 172 ppm closely matched the field reflectance from a California sample 9 of 2.1 × 10 4 cells ml −1 and less closely a red-snow sample from the Harding Icefield 10 , two studies that observed strong linear relationships between alga abundance and indices based on reflectance features in the 500-700 nm range. We, too, observed a strong linear relationship (NDI-alga model, …”
Section: Remote Sensing Of Microbial Impactmentioning
confidence: 64%
See 3 more Smart Citations
“…The spectrum at 333 ppm was similar in shape, but with lower values of reflectance, to a theoretical spectral albedo of snow with very high densities of algae 18 . The spectrum at 172 ppm closely matched the field reflectance from a California sample 9 of 2.1 × 10 4 cells ml −1 and less closely a red-snow sample from the Harding Icefield 10 , two studies that observed strong linear relationships between alga abundance and indices based on reflectance features in the 500-700 nm range. We, too, observed a strong linear relationship (NDI-alga model, …”
Section: Remote Sensing Of Microbial Impactmentioning
confidence: 64%
“…Experimental results presented here, together with previous correlative observations [8][9][10][11][12][13][14][15][16] , laboratory experiments 17 , and theoretical calculations 18 , provide a compelling case for the magnitude of the glacier microbiome's effect on hydrology and climate. Snow algae amplify their albedo reduction through life history, population growth, dispersal, and physiology.…”
Section: Implications For High-latitude Ice Sheetsmentioning
confidence: 99%
See 2 more Smart Citations
“…In these harsh environments, C. nivalis has 28 adapted to intense UV exposure by producing astaxanthin, a UV-screening pigment that 29 produces a visible red hue in snow (Gorton & 48 band ratios with wavelengths 630 -690 nanometers and 520 -600 nanometers, respectively, 49 were used to detect red snow in the satellite images. The spectral reflectance of red snow shows 50 that it has higher reflectance in the red band than in the green band, while the spectral reflectance 51 of snow and ice has higher reflectance in the green band than the red band (Takeuchi et al 2006). 52 Therefore, red to green reflectance band ratios that are less than 1.0 are more likely to signify 53 white snow or ice while band ratios that are greater than 1.0 are more likely to signify red snow 54 or ice.…”
Section: Introductionmentioning
confidence: 99%